Images of the Homeland in the Cultural Landscape of Northeast China - Ivanova, Alina (project baikal, 2023)
The article is based on the results of the 2023 field season in Northeast China. Three stories in the history of westernization of Manchuria are examined: the construction of railroads, the activities of Catholic missionaries, and the greening of the Liaodong Peninsula. It is concluded that the Jesuits managed to introduce the main architectural symbol of Western civilization, the Gothic cathedral, into the Chinese cultural landscape. Ideology proved to be more effective than faith in technical progress, which consistently guided both the Russians and the Japanese in their exploration of Manchuria.